Study guides

☆☆

Q: Factor x3 plus 2x2 plus 3x plus 6?

Write your answer...

Submit

Still have questions?

Related questions

x3 + 2x2 - 3x - 6 = (x2 - 3)(x + 2)

x(x + 1)(x - 3)

x3 - 2x2 + x - 2 =(x - 2)(x2 + 1)

X((x+1)^2)

(x-2)(x^2+3)

3 - 3x + x2 - x3 = (1 - x)(x2 + 3)

x3 + x2 - 3x - 3 x(x2 + x - 3) - 3

(x + 2)(x^2+4)

x3 - 2x2 - 4x + 8 = (x2 - 4)(x - 2) = (x + 2)(x - 2)(x - 2)

2x3 - 7 + 5x - x3 + 3x - x3 = 8x - 7

(2x + 1)(3x - 1)(3x - 1)

If that's 2x2, the answer is (x + 2)(x2 + 4)

x3 + 2x2 - 35x = x(x + 7)(x - 5)

x3 + 2x2 + 5x + 4 = (x + 1)(x2 + x + 4)

3x3 + 192 3(x3 + 64) ========

x3 + 2x2 - 8x + 5 = 0 x(2x - 8) + 5 = 0

Assuming simplify = factor...x3 - 3x + 2 = (x-1)(x2+x-2)

x3 + 2x2 - 35x = x(x2 + 2x - 35) = x(x + 7)(x - 5)

4X2+X3+3X+7Y+2X3 can only be simplified to 3X3+4X2+3X+7Y, because X3 and 2X3 are the only like terms.

(x4 - 2x3 + 2x2 + x + 4) / (x2 + x + 1)You can work this out using long division:x2 - 3x + 4___________________________x2 + x + 1 ) x4 - 2x3 + 2x2 + x + 4x4 + x3 + x2-3x3 + x2 + x-3x3 - 3x2 - 3x4x2 + 4x + 44x2 + 4x + 40Râˆ´ x4 - 2x3 + 2x2 + x + 4 = (x2 + x + 1)(x2 - 3x + 4)

2x2+7/x1

if that is suppose to be x3 - y12 then you can not factor this further if that is suppose to be 3x-12y then 3(x-4y) is the factored form

x3 + 2x2 - 19x - 20 = x3 + x2 + x2 + x - 20x - 20 = x2(x + 1) - x(x + 1) - 20(x + 1) = (x + 1)(x2 + x - 20) = (x + 1)(x - 4)(x + 5)

(x + 2)(x ^2 + 1)

(x - 3)(x2 + 3x + 3)